Experiment : Art in Brazil 1959 - 2000 - Bowron, Astrid; Aguilar, Nelson; Venancio Filho, Paulo (Oxford : Museum of Modern Art, 2001)
Caldas, Waltercio ; Camargo, Sergio ; Clark, Lygia ; Damasceno, José ; De Freitas, Iole ; Dias, Antonio ; Gross, Carmela ; Leirner, Jac ; Manuel, Antonio ; Neto, Ernesto ; Neuenschwander, Rivane ; Oiticica, Hélio ; Pape, Lygia ; Ramos, Nuno ; Rennó, Rosângela ; Resende, José ; Schendel, Mira ; Tunga
Experiment : Art in Brazil 1959 - 2000, The Museum of Modern Art, Oxford, 28 July - 21 October 2001
Engels
boek
Keywords: Brazilië